ENHANCING WRITING SKILLS OF EFL LEARNERS THROUGH AUTOMATED FEEDBACK: AN EMPIRICAL INVESTIGATION - Pariyanto; Tungka, Novalita Fransisca (Jurnal Ilmiah Spectral, 2024)
This study examines the effectiveness of an automated writing evaluation (AWE) tool in improving the writing skills of lower-proficiency EFL learners. The study involved 34 non-English major university students who received AWE feedback from the WhiteSmoke Writing Assistant during their writing practice sessions. The quality of their writing was evaluated using pre-and post-tests, and their perceptions of the feedback were gathered through a questionnaire. The results showed a significant improvement in the quality of students' writing after using AWE feedback. Additionally, the students perceived the AWE feedback as positively impacting the quality of their writing. These findings suggest that AWE feedback is a promising tool that can be incorporated into the writing class program to enhance the quality of students' writing. Writing teachers can use the tool to evaluate students' compositions and provide targeted feedback to help them improve their writing skills. Overall, the study highlights the potential of technology-based writing tools to facilitate language learning and improve EFL learners' writing proficiency.